2004
DOI: 10.4314/eamj.v81i7.9188
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in male cancer patients at Kenyatta National Hospital, Nairobi

Abstract: Background: The quality of life of cancer patients is likely to be influenced by psychological reactions of the cancer patients yet there are no documented issues related to quality of life in cancer patients in Kenyan hospitals. Objective: To investigate issues which affect the quality of life in male cancer patients. Design: Prospective cross sectional study. Setting: Kenyatta National Hospital, Nairobi, Kenya. Methods and subjects: Cancer patients above 12 years of age were interviewed during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The described experiences are partly in line with the findings from the two existing studies of cancer patients undergoing chemotherapy treatment in East Africa [5][6] . The study from Tanzania revealed that being diagnosed with and undergoing treatment for cancer often had a strong impact on health-related quality of life, causing multiple concerns regarding the need for care and support.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The described experiences are partly in line with the findings from the two existing studies of cancer patients undergoing chemotherapy treatment in East Africa [5][6] . The study from Tanzania revealed that being diagnosed with and undergoing treatment for cancer often had a strong impact on health-related quality of life, causing multiple concerns regarding the need for care and support.…”
Section: Discussionsupporting
confidence: 81%
“…Only two studies from East Africa have been found that describe patients' experiences of undergoing chemotherapy [5][6] . One of these publications studied Kenyan males by means of self-reported questionnaires and found that 93% of the participating men reported complaints regarding pain, inability to work and feeling miserable and that they expressed concerns regarding their families, health and work retardation 5 . The other publication had a mixed-methods design and investigated health-related quality of life among adult Tanzanians with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the literature demonstrated that the experience of living with cancer in Africa creates significant psychological problems for the affected patients and caregivers (Harding et al, 2011; Hameed, 2011). Common psychological problems include depression, difficulties in coping, poor self-image and self-esteem, loss, and sexual challenges (Harding et al, 2011; Kamau et al, 2007; Lavy, 2007; Mwanda et al, 2004).…”
Section: Palliative Care Situation In Africamentioning
confidence: 99%
“…Physical comfort, pain relief, proper nutrition, and an ability to carry out usual daily functions encompass the physical domain (Fitch, 2009). In the reviewed studies, such physical problems as pain, weight loss, fatigue, and shortness of breath were frequently experienced by palliative care patients with cancer (Mwanda et al, 2004). Among the reported physical symptoms, pain was most frequently experienced (Harding et al, 2011; Tapsfield & Jane Bates, 2011).…”
Section: Palliative Care Situation In Africamentioning
confidence: 99%
See 1 more Smart Citation